Facile synthesis of Mo/Al2O3–TiO2 catalysts using spray pyrolysis and their catalytic activity for hydrodeoxygenation. (15th February 2018) - Vo, The Ky; Kim, Woo-Sik; Kim, Seung-Soo; Yoo, Kye Sang; Kim, Jinsoo
Graphical abstract: Highlights: Facile synthesis of Mo/Al2 O3 −TiO2 catalysts by combining sol-gel and spray pyrolysis methods. Spherical micron-sized catalysts with well–dispersed Mo species on the Al2 O3 −TiO2 support. Effect of TiO2 concentration in the mixed oxide support on the catalytic activity and selectivity of HDO. HDO conversion of 100% and hexadecane selectivity of 93.18% over Mo/(80Al−20Ti) catalyst. Abstract: In this study, spherical mixed oxides of Al2 O3 and TiO2 supported molybdenum (Mo) catalysts, Mo/Al2 O3 −TiO2, were successfully prepared using a novel approach combining sol-gel and spray pyrolysis (SP) methods. First, both boehmite sol and titania sol were prepared by a sol-gel process, and then molybdate salt was dispersed in the sol mixture with the assistance of citric acid, followed by spray pyrolysis of the mixed precursor solution. Structural analyses of prepared catalysts showed that the dispersion of active sites was affected by the TiO2 concentration in the Al2 O3 −TiO2 mixed oxide support. The catalytic activities of reduced catalysts were investigated for hydrodeoxygenation (HDO) of palmitic acid, which is the main component of microalgae–derived biocrude. The results show that the Mo/Al2 O3 –TiO2 catalysts exhibited excellent catalytic performance for the HDO of palmitic acid.